Prevention of Venous Thromboembolism in Internal Medicine with Unfractionated or Low-molecular-weight Heparins: A Meta-analysis of Randomised Clinical Trials - Mismetti, Patrick; Laporte-Simitsidis, Silvy; Tardy, Bernard; Cucherat, Michel; Buchmüller, Andréa; Juillard-Delsart, Daphné; Decousus, Hervé (Thrombosis and Haemostasis, 2000)
The prevention of venous thromboembolic disease is less studied in medical patients than in surgery.We performed a meta-analysis of randomised trials studying prophylactic unfractionated heparin (UFH) or low-molecular-weight heparin (LMWH) in internal medicine, excluding acute myocardial infarction or ischaemic stroke. Deepvein thrombosis (DVT) systematically detected at the end of the treatment period, clinical pulmonary embolism (PE), death and major bleeding were recorded.Seven trials comparing a prophylactic heparin treatment to a control (15,095 patients) were selected. A significant decrease in DVT and in clinical PE were observed with heparins as compared to control (risk reductions = 56% and 58% respectively, p <0.001 in both cases), without significant difference in the incidence of major bleedings or deaths. Nine trials comparing LMWH to UFH (4,669 patients) were also included. No significant effect was observed on either DVT, clinical PE or mortality. However LMWH reduced by 52% the risk of major haemorrhage (p = 0.049).This meta-analysis, based on the pooling of data available for several heparins, shows that heparins are beneficial in the prevention of venous thromboembolism in internal medicine.
Keywords: Heparin; internal medicine; venous thromboembolism; prophylaxis; meta-analysis